145k views
1 vote
What is the solution to the equation Two-thirds x + 1 = one-sixth x minus 7? x = negative 16 x = negative 4 x = 4 x = 16

User PPK
by
5.9k points

2 Answers

5 votes

Answer:

x = -16

Explanation:

I was able to come to this conclusion by first giving
(1)/(6) and
(2)/(3) a common denominator.


(4)/(6) x +1 = (1)/(6)x -7

From here all I had to do was simply simplify on both sides so I subtracted
(1)/(6) from both sides of the equation and got


(3)/(6)x + 1 = -7

From the there I then subtracted the 1 from both sides of the equation so that the variable and the real number would be on different sides of the equal sign.


(3)/(6)x = -8

Then I had to isolate the
x so I divided both sides by
(3)/(6) and got -16.

User Rahul Gopinath
by
6.1k points
4 votes

Answer:

x = -16

Explanation:

Step 1: Write out equation

2/3x + 1 = 1/6x - 7

Step 2: Subtract 1/6x on both sides

1/2x + 1 = -7

Step 3: Subtract 1 on both sides

1/2x = -8

Step 4: Multiply 2 on both sides

x = -16

User David Steiman
by
6.0k points